Institutions and the location decisions of highly skilled migrants to Europe - Klaus Nowotny (University of Salzburg, Department of Social Sciences and Economics, 2013)
The economic literature provides ample evidence that immigration of highly skilled workers is beneficial for the host economy. Yet, when compared to countries such as the USA or Canada, Europe receives a lower share of migrants with tertiary education, raising concerns that the EU does not attract enough highly skilled migrants. There is, however, considerable heterogeneity in the share of highly-skilled migrants across EU-15 countries which is even more pronounced at the regional level. This paper uses this heterogeneity to investigate the economic, labor market and institutional factors that make regions and countries attractive for highly skilled migrants vis-à-vis low-skill migrants. Controlling for a variety of regional characteristics, the regressions show both similarities and differences in the determinants of location choice between high- and low-skilled migrants and possible directions for migration policy.
Keywords: F22; R23; C35; 330; highly-skilled migration; regional location decisions; institutions; migration policy